Pengaruh Technostress Dan Efikasi Diri Terhadap Kinerja Guru SMA Negeri Kecamatan Tapos - Ratih Novianty; Praesti Sedjo (FEB Universitas Maritim Semarang, 2023)
Teacher performance has the most important position in an effort to improve the quality of learning which will later affect the quality of graduates and will affect the achievement of national education goals. Some of the factors that can influence are self-efficacy and technostress. This study aims to determine the effect of partial and simultaneous technostress and self-efficacy on teacher performance. The study used quantitative research. Data retrieval techniques with questionnaires. The study population of all teachers who teach at Tapos Sub-District State High School is 100 teachers. The number of samples was determined using the Slovin formula and a sample of 80 people was obtained. Instrument test data analysis techniques use validity and reliability tests, linear regression analysis, classical assumption tests, Determination Coefficient Tests, and Hypothesis Tests with t tests and F tests. These findings are consistent with previous research showing that technostress affects teacher performance and self-efficacy also plays a role in improving teacher performance. In the context of the Covid-19 pandemic and distance learning, these factors have an important role to play in overcoming challenges in improving the quality of learning.